Public- Private- Partnership Policy: Proposed Nigerian Reform Programme for Electricity Development - Marcus, Samuel Nnamdi; Ayodele, A’sesan; Nnaoma, Iwu Hyacinth (American Journal of Humanities and Social Sciences, 2015)
The study examines the public private partnership policy in Nigeria as a panacea to the development and management of electricity in Nigeria. The study is descriptive and its objective is proposing an alternative policy that will ensure the sustainable development of electricity in Nigeria. The heavy presence of government in energy development did not seem to encourage desirable development in the sector. The SAP, Vision 2010, and NEP 1999 proposed deregulatory approach relying on private sector led development approach for the development of utilities. The NEEDS 2004 clearly and specifically proposes the PPP approach under the deregulatory devices. PPP as a contractual arrangement between the public and private sectors operators constitutes an approach to achieve well defined and shared objectives in a well-managed, cost-effective, efficient and sustainable manner, hence, is con-sidered in the paper. Findings suggest that forms of the PPP are given for consideration to bail Nigeria out of the impacts of poor quality, unreliable and limited availability of power-supply, presumed partly due to government led-development approach. The paper contains some policy issues such as the encouragement of private sector participation in the provision of energy infrastructure within the public- private- partnership policy (PPP) framework.